2005
DOI: 10.1029/2005jd006244
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric bromine chemistry and its impacts on ozone: A model study

Abstract: [1] An off-line three-dimensional tropospheric chemical transport model, parallelTropospheric Off-Line Model of Chemistry and Transport (p-TOMCAT), has been extended by incorporating a detailed bromine chemistry scheme that contains gas-phase reactions and heterogeneous reactions on both cloud particles and background aerosols. Bromine emission from bromocarbon photo-oxidation and from sea-salt bromine depletion and bromine removal through dry and wet deposition are included. Using this model, tropospheric bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
400
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(427 citation statements)
references
References 78 publications
25
400
2
Order By: Relevance
“…Following Yang et al (2005), we assume that 50 % of the bromide is released to the gas phase (leading to an additional factor of 0.5). The resulting time series of oceanic Br emissions is shown in Fig.…”
Section: Ocean-to-atmosphere Fluxesmentioning
confidence: 99%
“…Following Yang et al (2005), we assume that 50 % of the bromide is released to the gas phase (leading to an additional factor of 0.5). The resulting time series of oceanic Br emissions is shown in Fig.…”
Section: Ocean-to-atmosphere Fluxesmentioning
confidence: 99%
“…Lin et al [2006] suggested that Hg-Br chemistry is also significant in the upper troposphere. We present here a quantitative analysis of the global lifetime of Hg 0 against oxidation by tropospheric Br by combining the mechanism of Goodsite et al [2004] with Br concentrations from a global 3-D simulation of tropospheric bromine chemistry [Yang et al, 2005] as well as updated kinetic data. We find that oxidation by Br in the middle and upper troposphere could be an important sink for Hg 0 , and that the mechanism yields an atmospheric lifetime of Hg 0 consistent with observational constraints.…”
mentioning
confidence: 99%
“…However, oxidation by Br atoms is fast [Calvert and Lindberg, 2004;Goodsite et al, 2004]. Rapid chemical cycling between BrO and Br through BrO photolysis, selfreaction, and reaction with NO, balanced by Br oxidation by O 3 , maintains Br:BrO molar ratios of 0.01 -2 in the daytime troposphere [Platt and Janssen, 1995;Yang et al, 2005].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As there remains some uncertainty concerning atmospheric Hg oxidation process [35][36][37], simulations were also run including an oxidation mechanism based on bromine, with oxidant fields from the p-Tomcat model [38,39].…”
Section: Methodsmentioning
confidence: 99%